Body without organs: the aesthetic politics of becoming-animals in Jean Genet’s the balcony - Xiaoran Wang; Farideh Alizadeh (Cogent Arts & Humanities)
This article examines Genet’s exploration of aesthetic politics in The Balcony through the sensory redistribution, emphasizing how subversive aesthetic forces can establish a new sensory order to affirm equality amid conflict. While the role of the subject’s body—particularly through becoming-animal—serves as a crucial sensory force, its specific configuration remains insufficient. Focusing on the first three scenes, the analysis demonstrates that Genet constructs a foundational simulacrum, enabling the mutation of becoming-animal. This process involves increasing the separation between body and image, creating a Body without Organs (BwO) within the intensity difference. Such reconfiguration facilitates self-subversion and the renewal of aesthetic value while exposing the contingency inherent in identity politics within power relations. Drawing on Deleuze’s notions of becoming-animal and BwO, the article links these representations to the theory of simulacra, highlighting how The Balcony represents the body and image of the subject. Rancière’s aesthetic politics is further employed to elucidate the dual potential of becoming-animal in both aesthetic and political dimensions. Ultimately, the body operating within the simulacra configuration embodies an intensive BwO, fostering ongoing creation, transformation, and the realization of aesthetic politics’ transformative potential.